Effects of Iron and Vitamin E on Thickness of Carotid Artery Wall of Hyper Cholesterolemic Rabbits - GhR GH.R Dashti; M Mardani; B Rashidi; MJ Haeri (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Cardiovascular diseases are the main cause of morbidity and mortality in the developed countries. One of the indices of vascular injuries in atherosclerosis is proliferation and migration of smooth muscles of tunica media of arteries with lipids peroxidation by endothelial cells causing an increase in thickness of arterial wall. It is distinguished that iron can reduce antioxidant levels indirectly and also has a major effect in LDL per oxidation. As there is still doubt about anti-oxidative role of vitamin E in atherosclerosis formation, in this study, we observed the effect of vitamin E and iron on the thickness of the media of the carotid artery of hypercholestrolemic male rabbits.     Methods: Thirty white male rabbits were fed with cholesterol, Iron and Vitamin E for 42 days, and then these groups, and the carotid arteries were dissected. The samples were fixed in 10% formalin, and after tissue processing, serial sections were obtained, and H & E staining was done. Morphometrical studies were done by Motic Plus 2 and light microscope. Statistical analyses were conducted with SPSS software and ANOVA test.     Results: Intima-media thickness of arterial wall in those received iron and cholesterol, was significantly increased (p<0.05), but in the group receiving Vitamin E and cholesterol, this size was reduced (p<0.05).   Conclusion: According to our findings, Vitamin E due to its anti-oxidative effects on free radicals, was found to prevent arterial wall thickness, and thus has a protective role during atherosclerosis.